PENGARUH MEDIA GAMBAR DAN LAGU BUDDHIS TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA BUDDHA - Hariyanto Hariyanto (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aims to determine the differences in learning outcomes of Buddhist education at the elementary school level in Wonogiri Regency between learning using Buddhist pictures and songs as compared to learning through material presentation by teachers using textbooks. The research design used the Nonequivalent Control Group Design. The research subjects were third grade students of Buddhist elementary schools in Wonogiri Regency. The normality test uses the One-Sample Kolmogorov-Smirnov Test and the homogeneity test uses the Levence Test on SPSS. Meanwhile, to test the hypothesis using the Independent Sample T Test and Paired Sample T Test on SPSS. The results showed that the learning outcomes of the experimental group and the control group were normally distributed and homogeneous. The average increase in learning outcomes of the control group was 5.1250, the experimental group was 16.5000. The results of the independent sample t test show that Sig. (2-tailed) or p 0.000. Meanwhile, α 0.05, so p <αmeans that Ho is rejected. The results of the paired sample t test are known to be sig. (2-tailed) or p 0.000. While α 0.05 so p <α means that Ho is rejected, meaning that Buddhist images and songs have a more positive effect on learning outcomes